Constitutive Activity of TRPML2 and TRPML3 Channels versus Activation by Low Extracellular Sodium and Small Molecules - Grimm, Christian (American Society for Biochemistry and Molecular Biology, 2012)
The transient receptor potential channels TRPML2 and TRPML3 (MCOLN2 and MCOLN3) are nonselective cation channels. They are widely expressed in mammals. However, little is known about their physiological function(s) and activation mechanism(s). TRPML3 can be activated or rather de-inhibited by exposing it first to sodium-free extracellular solution and subsequently to high extracellular sodium. TRPML3 can also be activated by a variety of small chemical compounds identified in a high throughput screen and is inhibited by low pH. Furthermore, it was found that TRPML3 is constitutively active in low or no sodium-containing extracellular solution. This constitutive activity is independent of the intracellular presence of sodium, and whole-cell current densities are similar with pipette solutions containing cesium, potassium, or sodium. Here, we present mutagenesis data generated based on the hypothesis that negatively charged amino acids in the extracellular loops of TRPML3 may interfere with the observed sodium inhibition. We systematically mutated negatively charged amino acids in the first and second extracellular loops and found that mutating Glu-361 in the second loop has a significant impact on the sodium-mediated block of TRPML3. We further demonstrate that the TRPML3-related cation channel TRPML2 is also activated by lowering the extracellular sodium concentration as well as by a subset of small chemical compounds that were previously identified as activators of TRPML3, thus confirming the functional activity of TRPML2 at the plasma membrane and suggesting similar gating mechanisms for both TRPML channels.